2000
DOI: 10.1007/s004640000149
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hematological diagnosis on early and late outcome after laparoscopic splenectomyrid=""

Abstract: LS is a safe and reproducible procedure for most hematological indications, with a similar immediate outcome for benign diseases and a long-term hematological response comparable to the standard results that have been observed in open series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 12 publications
(21 reference statements)
1
29
0
4
Order By: Relevance
“…Lack of immediate and satisfactory post-splenectomy result or recurrence of thrombocytopenia are almost entirely connected with the remaining splenic tissue (7)(8)(9)(10)(11)(12)(13). Most authors, despite the use of different imaging techniques (ultrasonography, US; classic and spiral Computed Tomography, CT; and scintigraphy) underline the lack of reliable ways of preoperative assessment of ectopic splenic tissue (9, 10, 14, 15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of immediate and satisfactory post-splenectomy result or recurrence of thrombocytopenia are almost entirely connected with the remaining splenic tissue (7)(8)(9)(10)(11)(12)(13). Most authors, despite the use of different imaging techniques (ultrasonography, US; classic and spiral Computed Tomography, CT; and scintigraphy) underline the lack of reliable ways of preoperative assessment of ectopic splenic tissue (9, 10, 14, 15).…”
Section: Discussionmentioning
confidence: 99%
“…Targarona et al (20) reported the findings of an accessory spleen in 33% of the patient who had not clinical improvement after laparoscopic splenectomy for treatment of ITP. An association between the presence of missed accessory splenic tissue and recurrent or unresolved ITP after initial splenectomy has been reported (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic thrombocytopenic purpura is the most frequent indication for elective splenectomy [1,2,3,13,15,16,17]. The pathophysiology of the disease is associated with excessive destruction of the platelets within the spleen, liver or outside those organs, with the co-activity of antiplatelet antibodies [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic splenectomy (LS), however, first documented in a canine model and later performed successfully in humans by Delaitre (in Paris) [6], Carrol (in Los Angeles) [7], and Poulin (in Montreal) [8], is much less invasive, requiring three or four incisions of 2-10 mm. While several authors have reported success in performing LS in adults [9, 10,11,12,13,14,15,16,17,18,19,20,21,22,23] and in children [24,25,26,27,28], very few have exceeded 100 cases (Table 1) [9, 10,11,12,13,14,15,16,17,18,19,20,21,22,23]. Still, in these series LS has been consistently shown to be a safe and feasible procedure.…”
Section: Introductionmentioning
confidence: 86%